1992
DOI: 10.1152/jappl.1992.73.2.s33
|View full text |Cite
|
Sign up to set email alerts
|

Muscle sarcomere lesions and thrombosis after spaceflight and suspension unloading

Abstract: Spaceflight (flight) and tail suspension-hindlimb unloading (unloaded) produced significant decreases in fiber cross-sectional areas of the adductor longus (AL), a slow-twitch antigravity muscle. However, the mean wet weight of the flight AL muscles was near normal, whereas that of the suspension unloaded AL muscles was significantly reduced. Interstitial edema within the flight AL, but not in the unloaded AL, appeared to account for this apparent disagreement. In both experimental conditions, the slow-twitch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
84
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 0 publications
9
84
4
Order By: Relevance
“…Frozen sections were fixed in acetone, quenched in 0.3% H 2 O 2 in PBS, and then immersed in PBS containing 3% bovine serum albumin, 0.5% Tween-20, and 0.2% gelatin before immunolabeling with one of the following antibodies: (1) anti-ED1 ϩ (diluted 1:50; Bioproducts for Science, Indianapolis, IN), which binds an antigen specific for subpopulations of monocytes and macrophages [23], (2) anti-ED2 ϩ (diluted 1:100; Bioproducts for Science), which binds an antigen specific for a subpopulation of tissue macrophages [23], and (3) anti-W3/13 (diluted 1:100; Bioproducts for Science), which binds an antigen present on neutrophils and T cells; in these preparations T cells are scarce so virtually all of the cells recognized by anti-W3/13 in reloaded muscle are neutrophils [5]. Although anti-ED1 binds an antigen present in both monocytes and a subclass of tissue macrophages [23], in this investigation it is used as a macrophage marker because monocytes would remain in the vasculature and cells located within blood vessels were not included in the data obtained here.…”
Section: Analysis Of Time Course Of Inflammatory Cell Invasion Duringmentioning
confidence: 99%
See 1 more Smart Citation
“…Frozen sections were fixed in acetone, quenched in 0.3% H 2 O 2 in PBS, and then immersed in PBS containing 3% bovine serum albumin, 0.5% Tween-20, and 0.2% gelatin before immunolabeling with one of the following antibodies: (1) anti-ED1 ϩ (diluted 1:50; Bioproducts for Science, Indianapolis, IN), which binds an antigen specific for subpopulations of monocytes and macrophages [23], (2) anti-ED2 ϩ (diluted 1:100; Bioproducts for Science), which binds an antigen specific for a subpopulation of tissue macrophages [23], and (3) anti-W3/13 (diluted 1:100; Bioproducts for Science), which binds an antigen present on neutrophils and T cells; in these preparations T cells are scarce so virtually all of the cells recognized by anti-W3/13 in reloaded muscle are neutrophils [5]. Although anti-ED1 binds an antigen present in both monocytes and a subclass of tissue macrophages [23], in this investigation it is used as a macrophage marker because monocytes would remain in the vasculature and cells located within blood vessels were not included in the data obtained here.…”
Section: Analysis Of Time Course Of Inflammatory Cell Invasion Duringmentioning
confidence: 99%
“…Morphological observations support this general sequence of events in response to many different types of injuries, including crush injuries, strain injuries, freezing, exposure to toxins, and modified muscle use [3][4][5][6][7]. In each of these instances, the initial defect is thought to be damage to the muscle cell membrane, which allows unregulated influx of calcium into the damaged cell, thereby activating calpains that are capable of proteolyzing a wide variety of structural and regulatory proteins in muscle [8].…”
Section: Introductionmentioning
confidence: 97%
“…These disruptions to the normal structure and function of muscle are apparent within minutes after injury and may become more extensive during the following hours to days [2,[4][5][6]. Muscle injury also typically causes edema and the extravasation of neutrophils followed by ED1 ϩ macrophages and later the proliferation of resident ED2 ϩ macrophages [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we tested whether modifying NO production in vivo affects muscle inflammation and necrosis or influences the occurrence of inflammatory cell apoptosis during modified muscle use. Rats were subjected to periods of muscle unloading followed by reloading, which has been shown previously to cause muscle inflammation and necrosis [2,5,6] and inflammatory cell apoptosis [29]. Experimental manipulations were performed on animals to which NOS inhibitors were administered, and the concentrations of neutrophils, macrophages, necrotic fibers, and apoptotic inflammatory cells were compared to control animals not receiving NOS inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Important data from Riley et al 11 in the 8-11 hours following space flight revealed substantial eccentric contraction-like damage of muscle fibers in antigravity muscles which included hyperextension of sarcomeres with Aband filaments pulled apart and fragmented. These results have been replicated in a number of microgravity and simulated microgravity conditions (for a review see Riley et Table 1.…”
Section: Effects Of Zero Gravity On Functional Measures Of Skeletal Mmentioning
confidence: 99%